FEA Analysis of coupled thermo-mechanical response of grey cast iron material used in brake discs - Belhocine, Ali; Afzal, Asif (Revista Científica, 2019)
In this work, we will present numerical modeling using the ANSYS software adapted for finite element method, to follow the evolution of the global temperatures for the two types of brake discs, full and ventilated disc during a braking scenario. Also, the numerical simulation of the transient thermal analysis and the static structural one is performed here sequentially with the coupled thermo-structural method. A numerical procedure of calculation relies on important steps such that the CFD thermal analysis is well illustrated in 3D, showing the effects of heat distribution over the brake disc. This CFD analysis will help us in the calculation of the values of the thermal coefficients (h) that will be exploited in the 3D transient evolution of the brake disc temperatures. Three different brake disc materials were selected in this simulation and a comparative analysis of the results was conducted in order to derive the one with the best thermal behavior. Finally, the resolution of the coupled thermomechanical model allows us to visualize other important results of this research such as; the deformations, and the equivalent stresses of Von Mises of the disc, as well as the contact pressure of the brake pads. Following our analysis and the results we draw from it, we derive several conclusions. The choice will allow us to deliver the best suitable design of the brake rotor to ensure and guarantee the good braking performance of vehicles.